Disentangling Genetic Variation for Resistance and Endurance to Scuticociliatosis in Turbot Using Pedigree and Genomic Information - Saura, María; Carabaño, María J.; Fernández, Almudena; Cabaleiro, Santiago; Doeschl-Wilson, Andrea B.; Anacleto, Osvaldo; Maroso, Francesco; Millán, Adrián; Hermida, Miguel; Fernández, Carlos; Martínez, Paulino; Villanueva, Beatriz (Frontiers in Genetics, 2019)
Selective breeding for improving host responses to infectious pathogens is a promising option for disease control. Surviving an infectious challenge depends on two different host defense mechanisms, namely resistance (the ability of a host to avoid becoming infected or diseased) and endurance (the ability of an infected host to survive the infection), and both could be targeted for genetic improvement. However, it is currently not known how both traits contribute to survival, as reliable estimates of genetic parameters for both traits obtained simultaneously are scarce. A difficulty lies in obtaining endurance phenotypes for genetic analyses. In this study, we present the results from an innovative challenge test carried out in turbot whose design allowed disentangling the genetic basis of resistance and endurance to Philasterides dicentrarchi, a parasite causing scuticociliatosis that leads to very important economic losses in the aquaculture industry. A noticeable characteristic of the parasite is that it causes visual signs that can be used for disentangling resistance and endurance. Our results showed the existence of genetic variation for both traits (heritability = 0.26 and 0.12 for resistance and endurance, respectively) and for the composite trait resilience (heritability = 0.15), that includes both traits. The genetic correlation between resistance and resilience was very high (0.90) indicating that both are at a large extent the same trait but no significant genetic correlation was found between resistance and endurance. High-density SNP data obtained from 2b-RAD sequencing enabled genome-wide association analyses for detecting QTLs controlling the three traits. For endurance, one significant association was found at the linkage group 2. A candidate QTL region on linkage group 19 that explains 33% of the additive genetic variance was identified for resilience. The region contains relevant genes related to immune response and defense mechanisms. Although no significant associations were found for resistance, the pattern of association was the same as for resilience. To our knowledge, this is the first study in turbot disentangling the genetic basis of resistance and endurance to scuticociliatosis.